Indonesian Manuscripts from the Islands of Java, Madura, Bali and Lombok - Gallop, Annabel Teh (Islamic Studies Review, 2024)
Indonesian Manuscripts from the Islands of Java, Madura, Bali and Lombok (Dick van der Meij) Leiden & Boston: Brill, 2017, https://doi.org/10.56529/isr.v2i2.211